Hedge Ratio and Hedging Effectiveness in Indian Currency Futures Markets - N. Agrawal; P. Srinivasan (Финансы: теория и практика, 2024)
The purpose of the study is to assess the efficacy of diverse hedge ratios computed using three econometric models: OLS, VECM, and BEKK-GARCH model. This investigation centres on minimizing variance for the USD/INR currency pair within the Indian currency market, specifically during two distinct periods: the pre-COVID era and the COVID-19 era. Out-of-sample comparisons are conducted using the last 10 days of observations for both phases. The results of in- and out-of-sample evaluations demonstrate that the hedge approach established on OLS model outperforms alternative models in both periods. These findings offer valuable insights for investors, aiding in the enhancement of risk management strategies and informed decision-making with the objective of minimizing portfolio volatility and maximizing long-term returns.